Dynamic Response Analysis of an Asymmetric Coupled Vehicle-Track System Generated by Voided Elastic Two-Block Sleeper - Zhenxing He; Xinwen Yang (Shock and Vibration)
Based on vehicle-track coupled dynamic theory, a three-dimensional asymmetric vehicle-track coupling vibration model is developed to investigate the effect of voided elastic two-block sleepers on vehicle and track system dynamic responses. For the vehicle system, one car body, two frames, and four wheel sets are assumed to be rigid, with 35 degrees of freedom (DOF). For the track system, the rails and the concrete two-block sleepers are the main vibration components. The rails are modelled as Timoshenko beams, and the concrete two-block sleepers are assumed to be rigid mass with vertical and lateral movement. The pads under the rails and the rubber boots under the sleepers provide greater vertical and lateral elasticity for the track. The Hertz nonlinear elastic contact theory is used to calculate the normal wheel/rail force. The wheel/rail tangent creep force is first calculated using Kalker’s linear creep theory and then modified by the Shen-Hedrick-Elkins theory. The results show that the asymmetric voided elastic two-block sleepers have greater effects on the dynamic responses for fasteners and sleepers than on the car body and the wheel/rail forces under measured geometric irregularity and random irregularity. Two or more voided sleepers will greatly affect the vehicle running safety.